2021
DOI: 10.1128/jcm.03119-20
|View full text |Cite
|
Sign up to set email alerts
|

Verification and Validation of SARS-CoV-2 Assay Performance on the Abbott m 2000 and Alinity m Systems

Abstract: We verified the analytical performance of the Abbott RealTime SARS-CoV-2 assay on the m2000 system and compared its clinical performance to the CDC 2019-nCoV Real-Time PCR Diagnostic Panel and the ThermoFisher TaqPath RT-PCR COVID-19 kit. We also performed a bridging study comparing the RealTime SARS-CoV-2 assay with the new Abbott Alinity m SARS-CoV-2 assay. A number of standards, reference materials, and commercially available controls were used for the analytical verification to confirm the limit of detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 5 publications
2
20
0
Order By: Relevance
“…In 18/37 individuals with Alinity m SARS-CoV-2 / cobas 6800 SARS-CoV-2 discrepant results, previous and/or follow-up SARS-CoV-2 PCR result(s) were identified: 10/18 had a recorded previous SARS-CoV-2 PCR positive result in samples collected 0, 6, 8, 9, 9, 10, 11, 27, 59, 90 days (mean: 22.9 days; median: 9.5 days; range 0-90 days) before the sample in this study was collected (for multiple previous samples identified, the first previously positive sample was considered for each individual) and 8/18 had a recorded follow-up SARS-CoV-2 PCR positive result in samples collected 0, 0, 0, 2, 2, 5, 6, 7 days (mean: 2.8 days; median: 2 days; range 0-7 days) after the sample in this study was collected (for multiple follow-up samples identified, the first positive follow-up sample was considered for each individual). virus DNA; 13,17,19,21 (ii) quantitative detection of hepatitis C virus RNA; 12,17,18,21 (iii) quantitative detection of HIV-1 RNA; [15][16][17]21 (iv) qualitative detection of SARS-CoV-2 RNA; 20 (v) qualitative detection of 14 high-risk human papillomaviruses coupled with extended genotyping; 14,22 (vi) qualitative detection and differentiation of Chlamydia trachomatis, Trichomonas vaginalis, Mycoplasma genitalium, and Neisseria gonorrhoeae 23 and (vii) qualitative detection and differentiation of SARS-CoV-2, influenza A and B viruses, and respiratory syncytial virus. Twelve evaluations of Alinity m assays are available in peerreviewed literature, [12][13][14][15][16][17][18][19][20][21][22][23] but only a single analytical and clinical evaluation of Alinity m SARS-CoV-2 assay on a limited number of samples is known to have been published to date.…”
Section: An Insufficient Volume Of Leftover Specimens Prevented Retesting Of Samples With Discrepantmentioning
confidence: 99%
See 4 more Smart Citations
“…In 18/37 individuals with Alinity m SARS-CoV-2 / cobas 6800 SARS-CoV-2 discrepant results, previous and/or follow-up SARS-CoV-2 PCR result(s) were identified: 10/18 had a recorded previous SARS-CoV-2 PCR positive result in samples collected 0, 6, 8, 9, 9, 10, 11, 27, 59, 90 days (mean: 22.9 days; median: 9.5 days; range 0-90 days) before the sample in this study was collected (for multiple previous samples identified, the first previously positive sample was considered for each individual) and 8/18 had a recorded follow-up SARS-CoV-2 PCR positive result in samples collected 0, 0, 0, 2, 2, 5, 6, 7 days (mean: 2.8 days; median: 2 days; range 0-7 days) after the sample in this study was collected (for multiple follow-up samples identified, the first positive follow-up sample was considered for each individual). virus DNA; 13,17,19,21 (ii) quantitative detection of hepatitis C virus RNA; 12,17,18,21 (iii) quantitative detection of HIV-1 RNA; [15][16][17]21 (iv) qualitative detection of SARS-CoV-2 RNA; 20 (v) qualitative detection of 14 high-risk human papillomaviruses coupled with extended genotyping; 14,22 (vi) qualitative detection and differentiation of Chlamydia trachomatis, Trichomonas vaginalis, Mycoplasma genitalium, and Neisseria gonorrhoeae 23 and (vii) qualitative detection and differentiation of SARS-CoV-2, influenza A and B viruses, and respiratory syncytial virus. Twelve evaluations of Alinity m assays are available in peerreviewed literature, [12][13][14][15][16][17][18][19][20][21][22][23] but only a single analytical and clinical evaluation of Alinity m SARS-CoV-2 assay on a limited number of samples is known to have been published to date.…”
Section: An Insufficient Volume Of Leftover Specimens Prevented Retesting Of Samples With Discrepantmentioning
confidence: 99%
“…virus DNA; 13,17,19,21 (ii) quantitative detection of hepatitis C virus RNA; 12,17,18,21 (iii) quantitative detection of HIV-1 RNA; [15][16][17]21 (iv) qualitative detection of SARS-CoV-2 RNA; 20 (v) qualitative detection of 14 high-risk human papillomaviruses coupled with extended genotyping; 14,22 (vi) qualitative detection and differentiation of Chlamydia trachomatis, Trichomonas vaginalis, Mycoplasma genitalium, and Neisseria gonorrhoeae 23 and (vii) qualitative detection and differentiation of SARS-CoV-2, influenza A and B viruses, and respiratory syncytial virus. Twelve evaluations of Alinity m assays are available in peerreviewed literature, [12][13][14][15][16][17][18][19][20][21][22][23] but only a single analytical and clinical evaluation of Alinity m SARS-CoV-2 assay on a limited number of samples is known to have been published to date. 20 In that study, analytical verification of Alinity m SARS-CoV-2 confirmed the manufacturer's limit of detection claim of 100 copies/mL, with clinical evaluation performed on 203 residual nasopharyngeal swabs from symptomatic and asymptomatic individuals with suspected SARS-CoV-2 infection.…”
Section: An Insufficient Volume Of Leftover Specimens Prevented Retesting Of Samples With Discrepantmentioning
confidence: 99%
See 3 more Smart Citations